Process intensification of cellulase and bioethanol production from sugarcane bagasse via an integrated saccharification and fermentation process - Yoon, Li Wan; Ngoh, Gek Cheng; Chua, Adeline Seak May; Abdul Patah, Muhamad Fazly; Teoh, Wen Hui (Elsevier, 2019)
The production of value-added products such as cellulase and ethanol via a consolidated bioprocess could be realized by tapping into the multiple actions of a microbial community. For this purpose, an in situ saccharification and fermentation process through a sequential co-culture white-rot fungus and Saccharomyces cerevisiae on NaOH-pretreated sugarcane bagasse (SCB) was investigated. In the present work, white rot fungus plays a role in the production of cellulase enzymes. With the produced cellulase, an in situ saccharification process took place in the reactor to depolymerize pretreated SCB into reducing sugar. The reducing sugar was converted into ethanol via fermentation by S. cerevisiae, which was added into the system sequentially. White rot fungus Pycnoporus sanguineus was selected due to its competency in producing cellulase and reducing sugar production. The operating condition to maximize the production of reducing sugar in situ was obtained through a Central Composite Design method. A total of 3.13 g reducing sugar/100 g SCB was obtained when P. sanguineus was cultivated at 0.6% inoculum loading, 70% moisture content and 4 days. Subsequently, 4.5 g ethanol/100 g SCB was obtained from the in situ saccharification and fermentation system after S. cerevisiae was sequentially inoculated.